Security Enhancement for Smartphone Using Biometrics in Cyber-Physical Systems. (3rd April 2014) - Chae, Seung-Hoon; Moon, Daesung; Ko, Kyeong-Ri; Shin, JuHyun; Pan, Sung Bum
Abstract : With the expansion of the Cyber-Physical System (CPS) concept, smartphones have come to constitute a competitive platform that connects humans and the surrounding physical world. Along with the communication functions and mobility of cellular phones, smartphones have various sensors in addition to greatly enhanced performances and storage space compared with existing cellular phones. However the "unlock" process of smartphones and the need for user passwords when accessing SNSs prove to be great weaknesses in smartphone security. Therefore, smartphone security should be enhanced through biometrics, which can make up for the shortcomings of passwords. The present study proposes minutiae-ridge based fingerprint verification for enhancing the security of fingerprint verification, a biometrics, to improve smartphone security. To evaluate the proposed minutiae-ridge based fingerprint verification performance in smartphones, its performance was compared with existing fingerprint verification methods in terms of Equal Error Rate (EER), False Non-Match Rate (FNMR), and required number of cycles. The results show that although the required number of cycles increased by 1.5% with the proposed method, EER and FNMR improved by 53% and 92%, respectively.